Preservation of Arts through Training Gamelan Semar Pegulingan in the Batur Traditional Village | Pelestarian Seni Melalui Pelatihan Gamelan Semar Pegulingan di Desa Adat Batur - I Nengah Wirya Adnyana (GHURNITA: Jurnal Seni Karawitan, 2024)
Batur Traditional Village is a village located to the north of Bangli city, precisely in Kintamani District. Batur Traditional Village is an old traditional village characterized by the presence of many pelinggihs spread across the Batur area. In the field of arts, the Batur Traditional Village is famous for its old class gambelan, one of which is the Gong Gede gambelan. Based on observations, several other gambelan barungan such as gambelan angklung barungan and gambelan gambelan angklung barungan in the Batur Traditional Village are still observed, need to be improved and redeveloped, this is due to the lack of driving figures who focus on the field of art, especially musical art. Therefore, the Batur Traditional Village submitted a request via letter addressed to the Isi Denpasar Rectorate to help preserve art in the Batur Traditional Village. So, because of this problem, the writer was appointed and assigned by the Dean of the Faculty of Performing Arts to help preserve the arts in the Batur Traditional Village with the Thematic KKN program. The Thematic KKN program that the author will carry out in the Batur Traditional Village focuses on preserving the art of karawitan through percussion training, as well as to fulfill the final assignment the author created a work using Barungan Gambelan Semar Pegulingan entitled "Kelangon Ing Ranu".